Perancangan Strategi Untuk Meningkatan KepuasanPedagangDengan Metode SWOT Di Pasar Induk Lau Cih KotaMedan - Marbun, Santo Dohar (Industrial Engineering Online Journal, 2023)
ABSTRACTThe level of business competition is currently increasing. This situation can be seeninthemarket's uniformity of existing products and services, as well as the increasingly diversemarket developments. Pasar Induk Laucih Kota Medan is a traditional market that providesaplace and a service for traders to carry out trading activities, especially for vegetable andfruit traders. A strategy needs to be designed to increase customer satisfaction, in this case amongtraders at the Pasar Induk Lau Cih in Medan City. This study conducted a strategy designusing SWOT analysis that paid attention to internal and external factors at the Lau CihMainMarket in Medan City to find the right strategy for the Pasar Induk Lau Cih to increasecustomer satisfaction. The results of the study show that for the Pasar Induk Laucih, MedanCity is in quadrant II of the SWOT diagram, where this market has strengths but alsohasthreats that pose threats for the market to develop. Apart from that, from the SWOTmatrix, themost appropriate strategy to develop is the ST strategy, which means that the Pasar IndukLauCih must maximize its strengths to minimize the threats it faces to increase trader satisfaction. Furthermore, other strategies can also be used to impact customer satisfaction.Keywords : Strategy, Customer Satisfaction, SWOT Analysis